Water Footprint Assessment and Water-Energy-Food Nexus for Domestic and Institutional Sectors in Klang Valley, Malaysia: a Review - Safie, Nurul Azmah; Malek, M.A.; Noor, Z. Z. (International Journal of Engineering and Technology, 2018)
Change in climate, increasing world population and industrialization have placed considerable stress on water availability at certain places. Water Footprint accounting is a reliable technique that can be used for a better water management. This study focuses on establishing a doable methodology on water footprint accounting and assessment for direct water consumption from domestic and institutional sectors located in an urbanized environment such as Klang Valley, Kuala Lumpur. It includes investigation of Water Footprint at domestic household, schools, colleges, terminals and offices in Klang Valley. The value of water consumption, water production and water pollution will be determined using Hoekstra’s approach for green water, blue water and grey water. In addition, findings from this study will be linked to two other elements namely energy and food. This link is named as Water-Energy-Food Nexus. This study will establish the quantity and criteria of Water-Energy-Food Nexus specifically tailored to domestic and institutional sectors in Klang Valley.